2020
DOI: 10.1088/2515-7655/ab869e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental behaviour of a three-stage metal hydride hydrogen compressor

Abstract: A three-stage metal hydride hydrogen compressor (MHHC) system based in AB2-type alloys has been setup. Every stage can be considered as a Sieverts-type apparatus. The MHHC system can work in the pressure and temperature ranges comprised from vacuum to 250 bar and from RT to 200ºC, respectively. An efficient thermal management system was set up for the operational ranges of temperature designed. It dumps temperature shifts due to hydrogen expansion during stage coupling and hydrogen absorption/desorption in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Recently, a lab scale system consisting of a three stage MHHC was demonstrated at the Universitad Autónoma de Madrid. It is based on AB 2 materials used to compress the H 2 produced by a photo-electrolyser, with a typical output of less than 1 bar, up to 120 bar when the third stage is heated to 120 • C [76]. For this application, TiMn 2 type alloys were selected for all stages.…”
Section: Ab 2 Based Hydrogen Compressors For Pressures Of Up To 120/9...mentioning
confidence: 99%
“…Recently, a lab scale system consisting of a three stage MHHC was demonstrated at the Universitad Autónoma de Madrid. It is based on AB 2 materials used to compress the H 2 produced by a photo-electrolyser, with a typical output of less than 1 bar, up to 120 bar when the third stage is heated to 120 • C [76]. For this application, TiMn 2 type alloys were selected for all stages.…”
Section: Ab 2 Based Hydrogen Compressors For Pressures Of Up To 120/9...mentioning
confidence: 99%
“…The simplest layout of continuously operating two-stage H 2 compressor using four MH containers assembled in two modules and a check valve arrangement compression performances in prototype MH containers 33,43 or in compressor assembly. 45…”
Section: Metal Hydrite Materialsmentioning
confidence: 99%
“…Most of the articles related to hydrogen compression materials and published since 2015 consider multicomponent C14-AB 2±x intermetallics where A = Ti or Ti + Zr and B = Cr, Fe, V, Mn. [27][28][29][30][31][32][33][34][35][36][37][38] Certain attention has been paid to BCC alloys in V-Ti-Cr system, [39][40][41][42][43] multiphase C14 + BCC Ti-V-Mn alloys, 44 as well as AB 5type intermetallics. 22,45,46 Practically all the studies consider equilibrium pressure-composition-temperature (PCT) characteristics of hydrogen compression alloys when interacting with H 2 gas.…”
Section: Metal Hydrite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, AB 2 -type Ti-based Laves phase alloys exhibit a high hydrogen pressure, along with excellent hydrogen plateau characteristics and high hydrogen capacity . MHHCs employing AB 2 -type alloys are hence able to achieve hydrogen compression to much higher pressures at relatively lower temperatures. For example, Corgnale et al reported on a Ti 1.1 CrMn alloy for a hybrid MHHC with a hydrogen compression performance of 45 MPa at 413 K. Smith et al proposed a MHHC that employs a Ti 0.8 Zr 0.2 Fe 1.6 V 0.4 alloy and realizes a hydrogen compression of up to 80 MPa at around 433 K. According to the reports, it is noticeable that a high operation temperature and suitable organic fluid media for heat transfer are generally adopted on MHHCs employing V-based solid solutions or AB 5 -type alloys, in order to compress the hydrogen with a pressure much higher than their usual performance at moderate temperature. This is basically attributed to the relatively low hydrogen ab-/desorption pressure of these alloys.…”
Section: Introductionmentioning
confidence: 99%